Membangun Partisipasi Siswa Dalam Pemanfaatan Media Promosi Kesehatan Online Perilakuhidupsehat.Org Di SMK Pariwisata Sila Chandra Batubulan, Kecamatan Sukawati Kabupaten Gianyar Tahun 2019 - GA Dewi Kusumayanti; I Putu Suiraoka (Poltekkes Kemenkes Denpasar, 2020)
The opportunity to use the internet as a health promotion strategy is expected to improve the degree of public health. This technology is able to facilitate the delivery of information more closely, reaching healthy but irregular individuals in contact with health services. The purpose of this community service activity is to find out changes in knowledge about healthy living behaviors and participation in the use of online health promotion media